Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 2 - Derivatives - 2.5 The Chain Rule - 2.5 Exercises - Page 158: 40



Work Step by Step

$$g'(u)=\left([(u^2-1)^6-3u]^4\right)'=4[(u^2-1)^6-3u]^3((u^2-1)^6-3u)'= 4[(u^2-1)^6-3u]^3(6(u^2-1)^5(u^2-1)'-3)= 4[(u^2-1)^6-3u]^3(6(u^2-1)^5\cdot2u-3)=4[(u^2-1)^6-3u]^3(12u(u^2-1)^5-3)$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.